A STUDY ON JOB STRESS AMONG WOMEN EMPLOYEES IN BPO CENTER - et al., Dr.K.PRABHAKAR RAJKUMAR (International Journal of Advanced Science and Technology, 2019)
The increase in the number of women in the labor market signifies an important trend regarding women's employment. This has been occurring alongside increases in labor force and workforce, especially for urban women, although rural women workers predominate in terms of participation rates and overall magnitude. The main objectives of the study are to evaluate the stress management among the BPO personnel. Primary data have been collected through issue the questionnaire. The sample size of the study is claimed as 100 women employees working in BPO Center, Coimbatore. The study makes use of statistical techniques such as Percent analysis, Chi-square test and ANOVA in analyzing the data.  The study recommended that Governments should make it mandatory for companies to install Global Positioning System (GPS) in vehicles carrying women, in all industries which engage women in night shifts.